2021
DOI: 10.1038/s41598-021-83149-5
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and prognostic factors for intrahepatic cholangiocarcinoma: a population-based study

Abstract: We aimed to explore the clinicopathological features and survival-related factors for intrahepatic cholangiocarcinoma (ICC). Eligible data were extracted from the Surveillance, Epidemiology and End Results (SEER) database from 2004 to 2015. Totally, 4595 ICC patients were collected with a male to female ratio of nearly 1:1. The higher proportion of ICC patients was elderly, tumor size ≥ 5 cm and advanced AJCC stage. Most patients (79.2%) have no surgery, while low proportion of patients receiving radiotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…Early detection of ICC by screening is of vital importance in potential population with risk factors. Tumor size, R0 resection, lymph node metastasis, differentiation, adjuvant chemotherapy, CA19-9, T stage, PVTT, HBV infection/vaccination, and Eastern Cooperative Oncology Group performance status (ECOG-PS) have been reported as prognostic factors influencing survival outcomes of ICC in recent researches [ 2 , 31 , 37 , 40 , 56 – 58 ]. We identified NAR, tumor size >5 cm, multiple tumors, and poor differentiation as independent risk factors for OS in ICC patients undergoing hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Early detection of ICC by screening is of vital importance in potential population with risk factors. Tumor size, R0 resection, lymph node metastasis, differentiation, adjuvant chemotherapy, CA19-9, T stage, PVTT, HBV infection/vaccination, and Eastern Cooperative Oncology Group performance status (ECOG-PS) have been reported as prognostic factors influencing survival outcomes of ICC in recent researches [ 2 , 31 , 37 , 40 , 56 – 58 ]. We identified NAR, tumor size >5 cm, multiple tumors, and poor differentiation as independent risk factors for OS in ICC patients undergoing hepatectomy.…”
Section: Discussionmentioning
confidence: 99%
“…ICC is a malignant tumor derived from the bile duct epithelium and ranks second among the primary liver cancers. 1 , 18 The difference between ICC and extrahepatic cholangiocarcinoma is that ICC occurs in the liver parenchyma. Although the incidence of ICC worldwide is much lower than that of hepatocellular carcinoma (HCC), some recent studies have shown that the incidence of ICC has increased rapidly in the past few decades, and the mortality rate is still high.…”
Section: Discussionmentioning
confidence: 99%
“…Intrahepatic cholangiocarcinoma (ICC) is a very aggressive malignant tumor of the biliary tract, which is often diagnosed in the advanced stage. 1 2 Surgery is the main curative option. First-line chemotherapy is the preferred strategy in cases with macroscopic residual disease after surgery or locally recurrent or unresectable cholangiocarcinoma at the time of diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the vast majority of CCA occurs sporadically, without the presence of an underlying disease [ 10 , 13 ]. Merely a few prognostic factors have been investigated in recent years, including tumor size, surgery, pathological grade or Union for International Cancer Control (UICC) stage [ 14 ]. The role of liver fibrosis as a prognostic marker for survival is still controversially discussed [ 15 , 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%